Peningkatan Kemampuan Mengetik Siswa Melalui Penggunaan Aplikasi Typing Master Sebagai Media Pembelajaran - Marwan Marwan; Mira Wira Wardani (Jurnal Ecogen, 2023)
This study aims to find out to determine increase students' speed before using the application and after using the Typing Master application in the OTKP major at SMK Nusatama Padang, and improving students' typing accuracy before using the application and after using the Typing Master application in the OTKP major at SMK Nusatama Padang. This type of research is class action research (CAR). The research design used consisted of several cycle stages starting from the Pretest, Cycle I, Cycle II, and Posttest. This research was conducted on 19 students of class X OTKP 2 SMK Nusatama Padang. The instruments used are observation sheets and assessment sheets. Data collection techniques use observation, tests, and documentation. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The criterion for success in this research was the total number of students who passed the specified typing target, namely 70%, or as many as 14 students graduated from a total of 19 students with a speed of 80 cpm and 90% accuracy. Based on the results of each cycle there was an average increase in the number of students who reached the target, namely in Cycle I 73.68%, Cycle II 68.42%, Cycle III 73.68%, and Posttest 78.94%. That way it can be concluded that the use of the Typing Master application to increase the typing speed of class X OTKP 2 students is declared acceptable.